(untitled) (Al-Qamar, 2022)
Religion plays a very important role in life. But there are some who negate it and some who inherit it and some who adopt. While when academics talk about ethics, they are typically referring to decisions about right and wrong. In practice, ethics are decision-making tools that try to guide questions of human morality, by defining concepts such as good and bad, right and wrong, virtue and vice, justice and crime, etc. Various religions making claims about their belief systems being the best way for people to live, actively proselytizing and trying to convert unbelievers, etc. There always been some common properties in all human lives either they follow some religion or not. Here these properties have been discussed i.e. humans, humanity, basic human rights i.e. freedom, equality, self-defense, life, what life undergoes, death and after death rituals. With the reference what Quran says about all these things and the teachings of holy prophet Muhammad (peace be upon him) it has been proven that to some extent one need religion in his life because the creator lead us the way. The perspective of Islam has been discussed so that there is a way to build an ethical bond between all non-Muslims to a path of enlightenment and salvation.